2016
DOI: 10.1016/j.ijsu.2016.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone combined with other antiemetics versus single antiemetics for prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy: An updated systematic review and meta-analysis

Abstract: Dexamethasone combined with other antiemetics provided better prophylaxis than single antiemetics against postoperative nausea and vomiting after laparoscopic cholecystectomy. The underlying mechanism of dexamethasone action and its optimal dose should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…3 Moreover, it has been reported that laparoscopic surgery and surgical durations of more than 30 minutes may also increase the incidence of PONV. 22 Based on these factors, we chose female patients who planned to undergo gynecological laparoscopic surgery under general anesthesia as our study subjects. Since a history of PONV and a nonsmoking status are associated with a high incidence of PONV, [23][24][25] we allocated patients with a PONV history and nonsmoking patients equally into the oxycodone and sufentanil groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, it has been reported that laparoscopic surgery and surgical durations of more than 30 minutes may also increase the incidence of PONV. 22 Based on these factors, we chose female patients who planned to undergo gynecological laparoscopic surgery under general anesthesia as our study subjects. Since a history of PONV and a nonsmoking status are associated with a high incidence of PONV, [23][24][25] we allocated patients with a PONV history and nonsmoking patients equally into the oxycodone and sufentanil groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 pneumoperitoneum during laparoscopy leads to peritoneal stretching and irritation, which increase the risk of PONV. [ 17 ] Elevated ICP is also 1 of the risk factors for PONV. [ 18 ] Based on the results of this study, we can expect that TIVA will decrease the elevation of ICP compared to volatile agents and reduce the incidence of PONV in RALP.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Fujii and Nakayama [ 27 ] found that the rates of emesis-free effects were higher in 8 and 16 mg dexamethasone than in 4 mg dexamethasone. Awad et al [ 28 ] performed an updated meta-analysis and found that intravenous dexamethasone to antiemetic drugs increases their prophylactic effect against PONV after laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%